STATUS OF USE OF CONTRACEPTION BY WOMEN OF REPRODUCTIVE AGE - Габібова К. Г. (World of Medicine and Biology, 2015)
The purpose of the investigation was to study the status of use of contraceptives, reasons for their poor uptake by women in Azerbaijan. Material and methods. On the bases of 3 urban prenatal clinics and their surrounding schools and kindergartens conducted a survey of women. Only the questionnaire was distributed to 4000 women, the response rate was 1577 questionnaires. Results and discussion. The results of generalization of fully completed questionnaires show that a total of 812 respondents from 1577 women use contraceptives (51,5±1,3%), and constantly one of them use only 189 women (23,3±1,5%), 255 women-often (31,4±1,6%; t=3,70; P
Keywords: contraceptives; women of reproductive age; family planning